1999
DOI: 10.1021/bc9900441
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lysozyme-Estrone Glucuronide Conjugates. The Effect of the Coupling Reagent on the Substitution Level and Sites of Acylation

Abstract: Estrone glucuronide conjugates of hen egg white lysozyme were prepared by the mixed anhydride and active ester coupling procedures. Both methods gave good yields of conjugates, but the active ester procedure gave a more diverse range of products, making it less suitable for preparing conjugates for homogeneous enzyme immunoassay. Conjugation of lysozyme with estrone glucuronide by the mixed anhydride procedure gave one major derivative exclusively acylated at lysine residue 33 whereas conjugation by the active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 23 publications
8
29
2
Order By: Relevance
“…The reactivity of amine groups of lysozyme was investigated toward acetylation (Suckau et al, 1992), PEGylation (Lee and Park, 2003) and estrone glucuronide acylation (Smales et al, 1999) and in all cases the most reactive residues were Lys97 and Lys33, which corresponds to the highest accessibility values. The reactivity of each amine is therefore driven by the surrounding residues which affect the interaction potential of the lysine residues of interest.…”
Section: Site Specific Reactionmentioning
confidence: 99%
“…The reactivity of amine groups of lysozyme was investigated toward acetylation (Suckau et al, 1992), PEGylation (Lee and Park, 2003) and estrone glucuronide acylation (Smales et al, 1999) and in all cases the most reactive residues were Lys97 and Lys33, which corresponds to the highest accessibility values. The reactivity of each amine is therefore driven by the surrounding residues which affect the interaction potential of the lysine residues of interest.…”
Section: Site Specific Reactionmentioning
confidence: 99%
“…[48] Comparison with literature reports indicated that acetylation of HEWL with acetic anhydride occurred preferentially at Lys97 and Lys33, [49,50] which also display the highest area exposed to solvent (see Table 5). Acylation of HEWL with activated ester derivatives of estrone glucoronide [51] and pregnanediol glucoronide [52] also occurred at Lys33, Lys97, together with Lys116. Interestingly, the hydrophobic amine-targeted reagents (CO) 5 W(OMe)Me [19] and dinitrofluorobenzene [53] were also shown to react preferentially with Lys13, Lys33 and Lys116.…”
Section: Discussionmentioning
confidence: 95%
“…Also, the structural similarity of T4L with HEWL is relatively low and it would, therefore, also require much re-working of the reported conjugation and purification procedures. [4,5,7,23] The small increase in lytic rate obtained with TEWL ( Table 2) was insufficient to justify the work required to prepare and test TEWL-E1G conjugates for use as signal generators, even though it has high structural similarity with HEWL.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, estrone glucuronide (E1G) and pregnanediol glucuronide (PdG) conjugates of lysozyme have been used in the Ovarian Monitor [1] to monitor the main urinary estradiol and progesterone metabolites and, thus, define the fertile period of the human menstrual cycle. [1 -3,7] The most readily acylated lysine residues in HEWL (K33, K97 and K116) are all situated close to its welldefined active site cleft [4,5] and HEWL is relatively small compared to its bacterial cell substrate Micrococcus lysodeikticus (M. lysodeikticus). [6] Thus, the extensive inhibition on which the homogeneous enzyme immunoassay depends, [6] is believed to be due to steric hindrance of substrate access by antibody bound close to the active site cleft.…”
Section: Introductionmentioning
confidence: 99%